On finite-time stability of linear positive differential-algebraic delay equations - Nguyen H. Sau (2018)
IEEE This paper addresses finite-time stability of linear positive differential-algebraic equations with delay. Being different from the Lyapunov function method, delay-dependent sufficient conditions for positivity and finite-time stability of the system are established in terms of standard linear programming problems. A numerical example is given to illustrate the obtained results.